Pengaruh Pertumbuhan Ekonomi Dan Upah Minimum Kabupaten/Kota Terhadap Jumlah Pengangguran Di Provinsi Sumatera Utara - Staderlin, Mauren; Winata, Fidelya Rachael; Bianca, Kimberly Christa; Sianturi, Riko Fridolend; Purwati, Astri Ayu (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The economy of North Sumatra experienced deflation in 2020 due to the Covid-19 pandemic, leading to substantial declines across nearly all sectors and a decrease in employment opportunities. This study aims to examine the effects of economic growth and district/city minimum wages on the unemployment rate in North Sumatra Province. The research employs a quantitative method, encompassing a population of 25 districts and 8 cities in North Sumatra during the 2020-2022 period. The findings of this study are as follows: economic growth has a negative and insignificant effect on unemployment on a partial basis, district/city minimum wages have a positive and significant effect on unemployment on a partial basis, and collectively, both economic growth and district/city minimum wages have a positive and significant effect on the unemployment rate.